2011
DOI: 10.1038/emboj.2010.359
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis CUL4-DDB1 complex interacts with MSI1 and is required to maintainMEDEAparental imprinting

Abstract: Protein ubiquitylation regulates a broad variety of biological processes in all eukaryotes. Recent work identified a novel class of cullin-containing ubiquitin ligases (E3s) composed of CUL4, DDB1, and one WD40 protein, believed to act as a substrate receptor. Strikingly, CUL4-based E3 ligases (CRL4s) have important functions at the chromatin level, including responses to DNA damage in metazoans and plants and, in fission yeast, in heterochromatin silencing. Among putative CRL4 receptors we identified MULTICOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 73 publications
3
72
0
Order By: Relevance
“…Recent studies have shown that Cul4A, which binds to CRBN, plays a role in histone modification (12)(13)(14)(15). Moreover, analysis of the relative levels of Cul4A transcripts in multiple tissue types using the Novartis BioGPS expression array database (9) revealed that, like CRBN, Cul4A is expressed to the greatest extent in lymphoid cells (including CD4 + T cells) compared with other cell types (Fig.…”
Section: Crbn Controls Histone Modification Of Kcna3mentioning
confidence: 99%
“…Recent studies have shown that Cul4A, which binds to CRBN, plays a role in histone modification (12)(13)(14)(15). Moreover, analysis of the relative levels of Cul4A transcripts in multiple tissue types using the Novartis BioGPS expression array database (9) revealed that, like CRBN, Cul4A is expressed to the greatest extent in lymphoid cells (including CD4 + T cells) compared with other cell types (Fig.…”
Section: Crbn Controls Histone Modification Of Kcna3mentioning
confidence: 99%
“…We know that, in some cases, DNA methylation and H3K9me2 in heterochromatic regions act to reinforce each other, bypassing the role of RNAi in heterochromatin maintenance. Interestingly, mutants in DNA polymerase epsilon and cullin 4, components of the Clr4-containing CLRC complex in S. pombe, relieve silencing of some RNAi-sensitive transgenes in Arabidopsis, implicating that it is a cell-cycle-restricted process in plants as well (Yin et al 2009;del Olmo et al 2010;Dumbliauskas et al 2011;Pazhouhandeh et al 2011). Furthermore, some of these mutants have elevated levels of HR repair, and Ago2 itself has been implicated in HR repair of double-strand breaks (Wei et al 2012), reminiscent of the role of DNA replication and repair in heterochromatic silencing and spreading in S. pombe Zaratiegui et al 2011).…”
Section: Rnai and Heterochromatin Assemblymentioning
confidence: 99%
“…Mutation of Arabidopsis CUL4 affects embryo and endosperm development and leads to recessive seed abortion as well as a small decrease in male and female gametophyte transmission, indicating that CUL4 is essential for seed development (Dumbliauskas et al, 2011). Arabidopsis has two DDB1 paralogs sharing more than 90% protein identity: DDB1A and DDB1B, both interacting with CUL4 (Schroeder et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis has two DDB1 paralogs sharing more than 90% protein identity: DDB1A and DDB1B, both interacting with CUL4 (Schroeder et al, 2002). ddb1a ddb1b double mutants have shown a critical requirement for DDB1 function both in embryo development as well as gametophyte development or function (Bernhardt et al, 2010;Dumbliauskas et al, 2011). DDB1 proteins are adaptors that bridge CUL4 to the substrate receptors referred to as DDB1-CUL4 associated factor (DCAF) proteins (Angers et al, 2006;He et al, 2006;Higa et al, 2006;Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%